A new fusion approach for content based image retrieval with color histogram and local directional pattern - Zhou, J.; Liu, X.; Xu, T.; Gan, J.; Liu, Wan-Quan (Springer, 2018)
In this paper, we propose a novel color image retrieval approach by using an effective fusion of two types of histograms extracted from color and local directional pattern (LDP), respectively. First, we describe the extraction process of color histogram and LDP. Secondly we present these two features and then develop an effective fusion procedure including feature normalization and a new similarity metric. Thirdly, this new approach is validated after extensive comparisons with several existing state of the art approaches on two benchmark datasets including the Wang’s dataset and large size of the Corel-10000 dataset. Finally, a friendly interface for this proposed retrieval system is designed and used to show some retrieval results.